Critical managerial skills in the accommodation sector: The voice of the industry - Wessels, W.; du Plessis, E.; Slabbert, E. (South African Journal of Higher Education, 2023)
Dynamic labour structures within the tourism industry require employees to be adept and prepared for industry demands to deliver quality products. In South Africa, the role of tertiary institutions is to equip future tourism employees with these abilities; however, employers feel that graduates cannot fulfil industry’s demand, which creates challenges for students and tertiary institutions. As such, this research aimed to determine the managerial skills required by the accommodation sector in South Africa. The study’s findings reflect industry role players’ viewpoints regarding new graduates and their employability and may be utilised to improve current tourism management qualifications at tertiary education institutions.